Advances in nanotechnology and its applications - Jameel, Ahmad Tariq (Springer Singapore, 2020)
This book highlights current trends and research advances in nanotechnology and its applications. It discusses the synthesis and characterization of nanomaterials / nanocomposites for novel applications in environmental monitoring and sustainability, and presents new findings on wastewater treatment technologies using nanofiltration membranes.